Pre‐diagnostic circulating insulin‐like growth factor‐I and bladder cancer risk in the European Prospective Investigation into Cancer and Nutrition. Issue 10 (11th September 2018) - Lin, Crystal; Travis, Ruth C.; Appleby, Paul N.; Tipper, Sarah; Weiderpass, Elisabete; Chang‐Claude, Jenny; Gram, Inger T.; Kaaks, Rudolf; Kiemeney, Lambertus A.; Ljungberg, Börje; Tumino, Rosario; Tjønneland, Anne; et al.
Abstract : Previous in vitro and case–control studies have found an association between the insulin‐like growth factor (IGF)‐axis and bladder cancer risk. Circulating concentrations of IGF‐I have also been found to be associated with an increased risk of several cancer types; however, the relationship between pre‐diagnostic circulating IGF‐I concentrations and bladder cancer has never been studied prospectively. We investigated the association of pre‐diagnostic plasma concentrations of IGF‐I with risk of overall bladder cancer and urothelial cell carcinoma (UCC) in a case–control study nested within the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. A total of 843 men and women diagnosed with bladder cancer between 1992 and 2005 were matched with 843 controls by recruitment centre, sex, age at recruitment, date of blood collection, duration of follow‐up, time of day and fasting status at blood collection using an incidence density sampling protocol. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using conditional logistic regression with adjustment for smoking status. No association was found between pre‐diagnostic circulating IGF‐I concentration and overall bladder cancer risk (adjusted OR for highest versus lowest fourth: 0.91, 95% CI: 0.66–1.24, p trend = 0.40) or UCC ( n of cases = 776; 0.91, 0.65–1.26, p trend = 0.40). There was no significant evidence of heterogeneity in the association of IGF‐I with bladder cancer risk by tumour aggressiveness, sex, smoking status, or by time between blood collection and diagnosis ( p heterogeneity > 0.05 for all). This first prospective study indicates no evidence of an association between plasma IGF‐I concentrations and bladder cancer risk. Abstract : What's new? Past prospective studies have shown a positive association between circulating insulin‐like growth factor I (IGF‐I) concentration and colorectal, prostate, and breast cancer risk. However, the association between circulating IGF‐I concentrations and bladder cancer risk remains uncertain. Using a nested‐case control study with 843 bladder cancer cases across 9 European countries, for the first time here the authors examined prospectively the association between pre‐diagnostic circulating IGF‐I concentrations and bladder cancer risk. IGF‐I was not associated with overall risk of bladder cancer or urothelial cell carcinoma. Further prospective data, including on tumour aggressiveness, are required to examine the association in greater detail.